Varicose: a MAGUK required for the maturation and function of Drosophila septate junctions. - Moyer, K.E.; Jacobs, J.R. (BMC Developmental Biology, 2008)
Scaffolding proteins belonging to the membrane associated guanylate kinase (MAGUK) superfamily function as adapters linking cytoplasmic and cell surface proteins to the cytoskeleton to regulate cell-cell adhesion, cell-cell communication and signal transduction. We characterize here a Drosophila MAGUK member, Varicose (Vari), the homologue of vertebrate scaffolding protein PALS2.Varicose localizes to pleated septate junctions (pSJs) of all embryonic, ectodermally-derived epithelia and peripheral glia. In vari mutants, essential SJ proteins NeurexinIV and FasciclinIII are mislocalized basally and epithelia develop a leaky paracellular seal. In addition, vari mutants display irregular tracheal tube diameters and have reduced lumenal protein accumulation, suggesting involvement in tracheal morphogenesis. We found that Vari is distributed in the cytoplasm of the optic lobe neuroepithelium, as well as in a subset of neuroblasts and differentiated neurons of the nervous system. We reduced vari function during the development of adult epithelia with a partial rescue, RNA interference and generation of genetically mosaic tissue. All three approaches demonstrate that vari is required for the patterning and morphogenesis of adult epithelial hairs and bristles.Varicose is involved in scaffold assembly at the SJ and has a role in patterning and morphogenesis of adult epithelia.